Implementasi Nilai-Nilai Akhlak pada Lembaga Pendidikan Islam - Syamhadi Syamhadi; Rokhmadi Rokhmadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to examine in depth the implementation of moral values in Islamic educational institutions as a strategic step in shaping students who are not only intellectually intelligent, but also excel morally and spiritually. This research uses a qualitative approach with a library study type, through analysis of Islamic literature, articles on moral education, and relevant research results that discuss moral values. The results of the study indicate that the implementation of moral values in Islamic education includes three main aspects. First, morals towards Allah, including instilling piety, sincerity, and obedience through worship, spiritual habits, and strengthening religious ethics. Second, morals towards fellow human beings, which are realized by fostering honesty, justice, tolerance, empathy, and social responsibility through daily interactions, cooperation, and social activities. Third, morals towards nature, which includes instilling an attitude of love for the environment, preserving God's creation, and building ecological awareness as part of a Muslim's moral responsibility. Strategies for implementing moral values include integrating values into all subjects, providing role models by teachers and other educational staff, fostering positive behavior within the school environment, and continuously evaluating student attitudes and behavior. This strategy is designed to instill moral values not only at the cognitive level but also as concrete habits in daily life. This article's contribution lies in developing a conceptual and practical framework for building an Islamic education system oriented toward holistic character formation. With this approach, moral values are expected to be thoroughly internalized in students' personal, social, and environmental lives.